Предмет: Математика,
автор: kulicovmaksim12
Ш. Упростить выражение и найти значение выражения: (3x + 2)(2x - 1) – 3x (2x + 3) +2x, при х = -0,4 ДАЮ 20 БАЛЛОВ! ПОЖАЛУЙСТА ПОМОГИТЕ
Ответы
Автор ответа:
6
Ответ:
4,4
Пошаговое объяснение:
(3x + 2)(2x - 1) – 3x (2x + 3) +2x = = 6х²+4х-3х-2-6х²-9х+2х=
=-6х-2=-6*(-0,4)-2=4,4
Автор ответа:
0
Ответ:
6x² - 3x + 4x - 2 - 6x² - 9x + 2x
-3x + 4x - 2 - 9x + 2
-6x - 2
-0.4 × (-6) = 2,4
2,4 - 2 = 0,4
Похожие вопросы
Предмет: Физика,
автор: klepak
Предмет: Обществознание,
автор: angelinaangelin2
Предмет: Физика,
автор: islampermyakov
Предмет: Математика,
автор: зайка1911